ASTEROIDS SEARCH RESULTS IN LARGE PHOTOGRAPHIC SKY SURVEYS - Shatokhina, S. V.; Kazantseva, L. V.; Yizhakevych, O. M.; Eglitis, I.; Andruk, V. M. (Одеські астрономічні публікації, 2017)
Photographic observations of XX century contained numerous and varied information about all objects and events of the Universe fixed on plates. The original and interesting observations of small bodies of the Solar system in previous years can be selected and used for various scientific tasks. Existing databases and online services can help make such selection easily and quickly. The observations of chronologically earlier ppositions, photometric evaluation of brightness for long periods of time allow refining the orbits of asteroids and identifying various non-stationaries. Photographic observations of Northern Sky Survey project and observations of clusters in UBVR bands were used for global search for small bodies of Solar system. Total we founded 2486 positions of asteroids and 13 positions of comets. All positions were compared with ephemeris. It was found that 80 positions of asteroids have a moment of observation preceding their discovery, and 19 of them are chronologically the earliest observations of these asteroids in the world.